1967
DOI: 10.1366/000370267774385687
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Arc Studies for Alloy Analysis

Abstract: An evaluation of the plasma-arc spectrochemical technique for alloy analysis was made. Matrix effects were studied and found to be present at all concentrations investigated, but were not significant enough to preclude the use of one set of standards for any one particular base metal. The application of the technique for the analysis of aluminum, iron, nickel, and possibly cobalt base alloys has been demonstrated using identical operating conditions and with only three sets of standards. Tungsten was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
1971
1971

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A thesis by Bedrosian (40) was concerned with the effects of acids and surfactants on the analysis of solutions from plant tissues by the graphite spark method. Muntz (425) studied the analysis of alloys with the plasma jet, and concluded that maintenance of the nebulizer is the most serious problem with this source. Birks (47) summarized methods and results in the analysis of the actinide elements, including the problem of containment of radioactive materials, the merits of different excitation sources, and line interferences.…”
Section: Lasers and Microanalysismentioning
confidence: 99%
“…A thesis by Bedrosian (40) was concerned with the effects of acids and surfactants on the analysis of solutions from plant tissues by the graphite spark method. Muntz (425) studied the analysis of alloys with the plasma jet, and concluded that maintenance of the nebulizer is the most serious problem with this source. Birks (47) summarized methods and results in the analysis of the actinide elements, including the problem of containment of radioactive materials, the merits of different excitation sources, and line interferences.…”
Section: Lasers and Microanalysismentioning
confidence: 99%